Acetylcholinesterase immobilization and characterization, and comparison of the activity of the porous silicon-immobilized enzyme with its free counterpart. Issue 2 (16th March 2016) - Saleem, Muhammad; Rafiq, Muhammad; Seo, Sung-Yum; Lee, Ki Hwan
Abstract : The physically adsorbed acetylcholinesterase on mesoporous silicon surface is presented. The catalytic behavior of immobilized enzyme was assessed by spectrophotometric bioassay. The immobilization enhanced the reusability, shelf life and thermal as well as pH stability Abstract : A successful prescription is presented for acetylcholinesterase physically adsorbed on to a mesoporous silicon surface, with a promising hydrolytic response towards acetylthiocholine iodide. The catalytic behaviour of the immobilized enzyme was assessed by spectrophotometric bioassay using neostigmine methyl sulfate as a standard acetycholinesterase inhibitor. The surface modification was studied through field emission SEM, Fourier transform IR spectroscopy, energy-dispersive X-ray spectroscopy, cathode luminescence and X-ray photoelectron spectroscopy analysis, photoluminescence measurement and spectrophotometric bioassay. The porous silicon-immobilized enzyme not only yielded greater enzyme stability, but also significantly improved the native photoluminescence at room temperature of the bare porous silicon architecture. The results indicated the promising catalytic behaviour of immobilized enzyme compared with that of its free counterpart, with a greater stability, and that it aided reusability and easy separation from the reaction mixture. The porous silicon-immobilized enzyme was found to retain 50% of its activity, promising thermal stability up to 90°C, reusability for up to three cycles, pH stability over a broad pH of 4–9 and a shelf-life of 44 days, with an optimal hydrolytic response towards acetylthiocholine iodide at variable drug concentrations. On the basis of these findings, it was believed that the porous silicon-immobilized enzyme could be exploited as a reusable biocatalyst and for screening of acetylcholinesterase inhibitors from crude plant extracts and synthesized organic compounds. Moreover, the immobilized enzyme could offer a great deal as a viable biocatalyst in bioprocessing for the chemical and pharmaceutical industries, and bioremediation to enhance productivity and robustness.